Students' Perceptions of The Instagram Account @Ubahstigma As A Mental Health Education Platform - Indiarma, Verani; Aditia, Rafinita; Manalu, Primayanti (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2024)
Perception is the process by which individuals interpret, organize, and assign meaning to stimuli derived from experiences and learning. This research aims to analyze the perceptions of Bengkulu University students toward the Instagram account @ubahstigma as an educational source for mental health information. The theory used in this study is Perception Theory, which focuses on the process of receiving information and the factors that influence individual perceptions of the research subject. The study employs a qualitative method with a phenomenological approach. Informants were selected using purposive sampling based on criteria set by the researcher. The findings indicate that informants' perceptions are influenced by both internal and external factors, such as experience, background, expectations, hopes, and social changes. This research is expected to encourage more stakeholders to actively support the enhancement of educational resources related to mental health